Masjid Agung Kotagede: Kajian Awal Terhadap Inskripsi Yang Ada - Muhammad Chawari (Balai Arkeologi Yogyakarta, 1994)
Kotagede is one of the districts in Yogyakarta Municipality, which is located in the southeast of the city. In the past, Kotagede was the first capital of the Islamic Mataram kingdom. This place is an area given by the Sultan of Pajang (Hadiwijaya) to Ki Ageng Arrowing as a gift (Brandes, 1894: 415) for his victory over Aria Penangsang from Jipang. Therefore, it can be said that the Mataram kingdom was pioneered by Ki Ageng Pemanahan, then officially founded by Panembahan Senopati who occupied his palace in Kotagede. This area became the center of government during the Panembahan Senopati era and part of the Sultan Agung era. During the time of Sultan Agung the palace was moved to Kerto.